Implikasi Klinis Repolarisasi Dini - Reza Octavianus; Yoga Yuniadi; Budhi Setianto (The Indonesian Heart Association, 2012)
Early repolarization described as J-point elevation with concaved ST segment, notch or slurred at terminal QRS complex on surface electrokardiography. This electrokardiography pattern that usually exists in young male population, for about 60 years has been concluded as benign normal variant electrokardiography. Klatsky in 2002, has strengthed this issues with his study with 1000 elecrokardiographies with early repolarization which were followed for 12 years. There was no significant case for hospitality or malignant ventricular arrhythmias among population with early repolarization comparared with normal elektrokardiography without early repolarization.But, recent studies with larger samples, show different thing, which is there was a correlation between early repolarization and malignat ventricular arrhythmias. So the issue is, whether we can still consider this early repolarization as a normal variant or not. And how about the management of asymptomatic population with early repolarization such as syncope or evidence of malignant ventricular arrhythmias.T-wave Alternans is a difference at amplitude or morphology of ST segment and T wave in every other heart beat. T-wave Alternans measurement is a non-invasive method to value cardiac cells hererogeneity. This examination has been proven to be useful as a risk stratification for malignant ventricular arrhythmias events in large studies. Higher T-wave Alternans value accompanied with higher risk for developing these arrythymias. T-wave Alternans measurement has been approved in the guideline for management of wide QRS complex tachyarrythmias for detection ventricular arrhythmias with I and IIa class of recommedantion. The more practical Modified Moving Average technicque which can be performed in healthy subjects with early repolarization is useful for risk stratification. Large studies have approved the use of Modified Moving Average for measure T-wave Alternans in these arrhythmias risk stratification.